Comparison of vincristine, carmustine, melphalan, cyclophosphamide, prednisone (VBMCP) and interferon-α with melphalan and prednisone (MP) and interferon-α (IFN-α in patients with good-prognosis multiple myeloma: A prospective randomized study - Zervas, K.; Pouli, A.; Gregoraki, B.; Anagnostopoulos, N.; Dimopoulos, M.A.; Bourantas, K.; Tzilianos, M.; Barbarousi, D.; Venetis, E.; Vyniou, N.; Maniatis, A. (European Journal of Haematology, 2001)
Objectives: The purpose of the study was to evaluate, in a selected group of myeloma patients with favorable prognosis, the effect, on response and survival, of polychymotherapy compared with melphalan-prednisone, plus interferon in both arms. Methods: Eighty-nine previously untreated patients with multiple myeloma and prognostic factors indicating a good prognosis were randomized to either oral melphalan plus prednisone (MP) in combination with recombinant interferon-α (rIFN-α) or combination chemotherapy with vincristine, carmustine, melphalan, cyclophosphamide, and prednisone (VBMCP) alternating with rIFN-α. The two treatment groups were comparable in terms of pretreatment characteristics. Results: The overall response rate was 67.4% (2.3% complete remission, 65.1% partial response) in the MP/IFN-α group and 69.1% (14.3% complete remission, 54.8% partial response) in the VBMCP/IFN-α group (p = 0.59). There were no differences also in response duration and overall survival between the two treatment groups. The median response duration was 39.1 months in the MP/IFN-α group and was not reached in the VBMCP/IFN-α group (p = 0.6). Overall survival was long in both treatment groups. The estimated 5-yr survival was 66% and 62% in the MP/IFN-α and VBMCP/IFN-α group, respectively (p = 0.8). Toxicity was modest and treatments were well tolerated. Neutropenia (WHO grade 3 or 4) was higher, but not statistically significant, in the VBMCP/IFN-α group. Conclusions: The results of the study show that in myeloma patients with good prognosis, combination chemotherapy alternating with interferon-α has no advantage over conventional MP plus interferon-α, in regard to response rate, response duration, and overall survival of patients. © Munksgaard 2001.
Keywords: Chemotherapy; Interferon-α; myeloma; Prognostic factors